Wet Curtain Wall: A Novel Passive Radiant System for Hot and Dry Climates. (May 2017) - Butera, F.; Aste, N.; Adhikari, R.S.; Del Pero, C.; Leonforte, F.; Zanelli, A.
Abstract: This paper proposes a novel radiative passive system for hot and dry climates to improve outdoor thermal comfort. The solution consists in a curtain, characterized by two different finishing surfaces, one is waterproof and the other one is absorbent, immersed in a water tank by means of a mechanized system and subsequently used as a radiant surface with reduced temperature thanks to evaporative cooling effect. The effectiveness of the proposed system is verified by means of CFD simulations carried out on a sample application in outdoor space and supported by experimental measurements carried out on a small sample of curtain. The results showed that the proposed system can reduce the operative temperature up to 6°C with respect to the testing conditions (air temperature of 28.5°C and relative humidity of 50.5%) ensuring higher comfort levels and a limited water consumption to keep the curtain constantly wet (25 l/h for 130m 2 of wet curtain).